Effectiveness of Affirmation Stress Management on The Stress level Among Caregivers of Shizophrenia Patient - Mulyanti Ners; Brune Indah Yulitasari; Tri Paryati (Alma Ata University Press, 2020)
Schizophrenia is a chronic and severe disease so they need caregivers to help their daily activities. Caregivers of patients with schizophrenia have experienced chronic stress in their daily lives. The effects of caregiver of Schizophrenia with high stress level are the disruption of family relationships, constraints in social, leisure and work activities, financial difficulties, and negative impact on their own physical health. Affirmation stress management one of the intervention to reduce the level stress on caregiver of patients with Schizophrenia.This study aimed to prove effect affirmation stress management on the stress level among caregivers of Schizophrenia people.This research was quasi-experimental with one group pretest-postest without control. Subjects of this study were 29 caregivers of schizophrenia patients. Subjects selection technique used purposive sampling. Measuring instruments used perceived stress scale. The technique of data analysis used correlation of paired t-test. The results showed that the average level of stress caregiver before the stress management action was 15.17 (SD: 6.54) and the average stress level after the action was 13.59 (5.39). Statistical test results showed that there were significant differences between the stress level values before and after the affirmative stress management intervention was given (p. Value = 0.015). The conclusion of this research is there was an influence of affirmation stress management on stress level on caregivers of Schizophrenia patient.